1998
DOI: 10.1161/01.hyp.32.6.1098
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Flow-Induced Dilation and Increased Production of cGMP in Spontaneously Hypertensive Rats

Abstract: Abstract-We investigated flow (shear stress)-and agonist-induced cGMP release in mesenteric vascular beds of spontaneously hypertensive rats (SHR) and normotensive Wistar Kyoto rats (WKY). The mesenteric vascular bed was perfused in situ with Tyrode's solution. Vascular relaxation and cGMP release in the perfusate were determined on stimulation by flow or by acetylcholine (0.1 mol/L) or sodium nitroprusside (0.1 mmol/L). Flow-induced release of cGMP was significantly greater in SHR than in WKY (PϽ0.01), despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
6
14
0
Order By: Relevance
“…In the present study, the enhanced extent of hypotension in SHR did not change after administration of molsidomine or PETN. The present findings are similar to those obtained in NO-deficient hypertension (6,8) although the etiopathogenic background, NO production, NO level, and cGMP level are different in these two experimental models of hypertension (29).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the enhanced extent of hypotension in SHR did not change after administration of molsidomine or PETN. The present findings are similar to those obtained in NO-deficient hypertension (6,8) although the etiopathogenic background, NO production, NO level, and cGMP level are different in these two experimental models of hypertension (29).…”
Section: Discussionsupporting
confidence: 90%
“…For example, it is well known that flow-induced dilation involves nitric oxide release from endothelial cells, which is significantly altered in different arterial beds in hypertensive rats [27,28]. However, Qiu et al have shown a significant decrease in flow-induced dilation and at the same time an increase in cGMP production from endothelial mesenteric arteries in spontaneously hypertensive rats [29]. Our data may suggest that the response to nitric oxide, in addition its production, could be altered in hypertension thereby affecting the level of ERK1/2 MAP-kinase phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SNP releases NO after intracellular metabolism in the vascular smooth muscle cells (VSMCs), leading to relaxation via a cyclic guanosine monophosphate-dependent mechanism [21]. Fig.…”
Section: Effects Of Fas On Endothelium-independent Vascular Relaxatiomentioning
confidence: 99%